Assessment of Resources of Children and Youth in Conﬂict with the Community Norms - Hrnčić, Jasna H.; Marčetić Radunović, Gordana N. (Sociološki pregled, 2018)
The paper presents a research conducted in order to analyze the representation of resources of children and youth in conﬂict with community norms in diﬀerent domains, and to develop an instrument for their comprehensive and rapid assessment in research and prevention programs. A questionnaire, the List of Strengths of Children and Youth in Conﬂict with Community Norms - LS1, was applied by 32 experts from 9 centers for social work in the assessment of 67 persons aged 11 to 20, referred there due to suspicion of antisocial behavior. The highest representation of resources was obtained in the peer and family groups, and the lowest at work and at school. The LS1 has shown high reliability and a good constructive, convergent and criterion validity, as well as usefulness in practical application. Based on expert suggestions, the LS1 was revised in the LS2 questionnaire.
Keywords: assessment of strengths; protective factors; resources of children; children in conﬂict with the law